Delivering Context-Specific Agro-Advisories and Climate-Smart Practices to Last-Mile Beneficiaries for Effective Climate Risk Management in Senegal - Akinseye, Folorunso Mathew; Kebe, Amy; Faye, Aliou; Emanuel, Jacob; Worou, Nadine; Kumar, Shalander; Whitbread, Anthony; Wane, Abdrahmane (International Livestock Research Institute, 2025)
This document presents the progress made by the AICCRA-Senegal project in disseminating climate-smart technologies and services through integrated approaches combining data, research and public-private partnerships. Interventions carried out in collaboration with ANACIM, ILRI, ISRA-CERAAS, ANCAR and the private sector (Jokalante) have enabled the deployment of digital platforms such as AgData Hub and iSAT, which provide access to local weather forecasts and agro-climatic advice in national languages. More than 5,000 producers receive weekly voice messages via WhatsApp and SMS, while community radio stations reach more than 80,000 listeners. Evaluations show yield increases of 21% to 41% for millet and groundnuts, demonstrating the combined effectiveness of climate advice and CSA practices. At the same time, more than 300 demonstration plots have been used to test integrated fertilisation (ISFM) and adapted sowing windows. These actions strengthen climate resilience, local decision-making and institutional capacities around agricultural risk management in Senegal.